2014
DOI: 10.3390/nu6051931
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Activities of the Sesame Oil and Sesamin

Abstract: Sesame oil is widely consumed as nutritious food, cooking oil, and in pharmaceuticals and food. In this study, the antinociceptive and anti-inflammatory properties of the sesame oil and sesamin were investigated. The sesame oil and sesamin reduced the number of abdominal contortions at the doses 100, 200, or 400 mg/kg. The first and second phases of the time paw licking were inhibited by sesame oil and sesamin (100, 200, or 400 mg/kg). After 90 min of treatment, sesame oil and sesamin increased the reaction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 48 publications
2
63
0
1
Order By: Relevance
“…Substance= Rotation velocity of cylinder 0.0358 -Radius of rotation 0.0943 + 1.11 (Rotation velocity of cylinder Radius of rotation) + 6.45 (4) According to Figures 4, it can be claimed that the speed of centrifuges and the radius of the rotating cylinder are correlated with the amount of solids (debris) of sesame oil. Using a cylinder with a radius of 175 mm, it was observed that the highest amount of pulp in the sesame seed oil was at 3500 and 7.4 percent, and the lowest amount of pulp in the 5500 and 4.4 percent, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substance= Rotation velocity of cylinder 0.0358 -Radius of rotation 0.0943 + 1.11 (Rotation velocity of cylinder Radius of rotation) + 6.45 (4) According to Figures 4, it can be claimed that the speed of centrifuges and the radius of the rotating cylinder are correlated with the amount of solids (debris) of sesame oil. Using a cylinder with a radius of 175 mm, it was observed that the highest amount of pulp in the sesame seed oil was at 3500 and 7.4 percent, and the lowest amount of pulp in the 5500 and 4.4 percent, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This oil has a long and lasting resistance to high-fat unsaturated edible oils [3]. The natural antioxidants in this oil have a high resistance to oxidation and valuable physiological properties of sesame oil [4]. Sesame seeds contain 30-50% oil and 20-30% protein [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that lignans (artigenin, arctiin, and lappaol F) of Arctium lappa (burdock) could hamper the expression of various proinflammatory cytokines such as IL‐6, TNF‐α via inhibiting nuclear factor kappa B (NF‐κB) in different models . Monteiro and his colleagues concluded that sesame oil and sesamin (lignin) could impede leukocyte migration or infiltration as well as downregulate various proinflammatory cytokines due to the rich content of PUFA and thus confer its anti‐inflammatory activity . However, CLAR also lowered the inflammatory response owing to its bacteriostatic and anti‐adhesion properties .…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Monteiro and his colleagues concluded that sesame oil and sesamin (lignin) could impede leukocyte migration or infiltration as well as downregulate various proinflammatory cytokines due to the rich content of PUFA and thus confer its anti-inflammatory activity. 33 However, CLAR also lowered the inflammatory response owing to its bacteriostatic and anti-adhesion properties. 34 The results of this in vitro studies emphasize that burdock complex can exhibit anti-adhesive and anti-inflammatory activities and thus abolish H. pylori infection without displaying direct bactericidal property.…”
Section: Discussionmentioning
confidence: 99%
“…Sesamin, one of the major lignans in sesame seed and flax, possesses various beneficial functions, including anti-oxidative [105], lipid-lowering (arachidonic acid [106] and cholesterol [107] levels), anti-hypertensive [108], neuroprotective [109], anti-tumor [110], and anti-inflammatory [111] actions. Sesamin also plays a unique role in improving the bioavailability of T3 in vitro [112] and in vivo [113].…”
Section: Synergistic Anti-proliferative Effects Of T3 and Dietary mentioning
confidence: 99%